The concept and application of corporate Waqf in Malaysia / Nur Sakinah Hayani Mohd Rahman - Mohd Rahman, Nur Sakinah Hayani (Academy of Contemporary Islamic Studies (ACIS), 2016)
Waqf is a medium of distributing wealth that has been practiced since the time of the Prophet s.a.w. This practice is demand in Islam because its benefit could be gained, not only in the world but in the hereafter as well. Waqf is also important in fostering a spirit of ukhuwah among individuals without expecting anything in return. When someone has donated his property, individuals who use it do not have to replace or return it back to its original owner. So, the property remains as long as the benefits of the property ownership can still be used. Accordingly, there are numerous modern innovations have been implemented to waqf in Malaysia including the introduction of corporate endowment. Corporate endowment is the latest innovation in the world of Islamic finance. The practice of corporate waqf allows the contributors to donate not only by using fixed asset such as land and building but also by liquidity. Then, the liquidity will be invest by corporate waqf entity before distribute it to the beneficiaries. Furthermore, the practice of corporate endowments is in line with the Quran and Sunnah and do not conflict with the laws and regulations set by the sharia. This paper aims to explore the details regarding the concept of corporate waqf that have been establish in Malaysia since 2006, as well as the modus operandi of the practice of corporate waqf entity